Provenance Evolution of Age-Calibrated Strata Reveals When and How South China Block Collided With Gondwana - Yang, C.; Li, X.H.; Li, Zheng-Xiang; Zhu, M.; Lu, K. (AMER GEOPHYSICAL UNION, 2020)
The South China Block (SCB) has been regarded by many as an integral part of Gondwana, but proposed timing and processes for its accretion to Gondwana vary and remain contentious, largely owing to the lack of reliable Pan-African age paleomagnetic data and tectono-magmatic records from the SCB. Integrated in situ U-Pb ages and Hf-O isotope analyses of detrital zircons from geochronologically well-calibrated Ediacaran-Cambrian sedimentary rocks of western SCB reveal age populations of 2.51, 1.85, 1.20, 0.80, and 0.52 Ga. Detrital zircon age spectra indicate a major tectonic transition for the SCB during 0.56–0.54 Ga, interpreted to reflect the beginning of the collision between SCB-Indochina and NW India blocks. The collisional event lasted until early Ordovician, leading to the suturing of the SCB-Indochina to the northern margin of East Gondwana.